But Dmitry did no wrong. (Economist, 2001)
Reports on the protests over the arrest of Dmitry Sklyarov, a Russian programmer, by the United States Federal Bureau of Investigation in July 2001 after he delivered a paper at a computer conference in Las Vegas, Nevada. Details of the case involving the 1998 Digital Millennium Copyright Act (DCMA) and a program that circumvented some of the limits on the Adobe Systems eBook Reader software; Efforts of computer scientist Edward Felten to challenge the constitutionality of the DMCA.